IoT based Edge Computing - Bansal, Malti; Harshit (Journal of Trends in Computer Science and Smart Technology, 2021)
Edge computing is a new way of calculating where most computer and storage devices are located on the internet, near mobile devices, sensors, end users, and internet of things devices. This physical approach improves delays, bandwidth, trust and survival.